1981
DOI: 10.1007/bf03189516
|View full text |Cite
|
Sign up to set email alerts
|

On the pharmacokinetics of domperidone in animals and man IV. The pharmacokinetics of intravenous domperidone and its bioavailability in man following intramuscular, oral and rectal administration

Abstract: The pharmacokinetics and bioavailability of domperidone, a novel gastrokinetic, were studied in healthy male subjects by comparing plasma concentrations and urinary excretion following intravenous, intramuscular, oral and rectal administration. Two oral dosage forms were studied: 10-mg tablets and a 10-mg/ml oral solution. The influence of a meal on the oral bioavailability and the dose-proportionality were also investigated. Plasma levels of intravenous domperidone could be described by a three-compartment mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 12 publications
(23 reference statements)
2
60
1
Order By: Relevance
“…Domperidone is known to undergo rapid and complete absorption from gut 57,58 . The drug plasma concentration declined rapidly thereafter with no drug being detected beyond 8 h. Domperidone undergoes rapid first pass metabolism though renal clearance is low 59 .…”
Section: Iv) In-vivo Pharmacokinetic Studies Of Domperidonementioning
confidence: 99%
“…Domperidone is known to undergo rapid and complete absorption from gut 57,58 . The drug plasma concentration declined rapidly thereafter with no drug being detected beyond 8 h. Domperidone undergoes rapid first pass metabolism though renal clearance is low 59 .…”
Section: Iv) In-vivo Pharmacokinetic Studies Of Domperidonementioning
confidence: 99%
“…It is transferred to maternal milk in slight quantities due to its high molecular weight and its 90% binding to plasma proteins (30). After administering 10 mg of domperidone 3 times a day for 4 days Hofmeyer et al found a concentration in serum and in milk, of 10 and 2.6 ng/ml respectively (31).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Trials are now urgently needed to establish optimal oral and rectal dosing schedules against a variety of emetogenic chemotherapy regimes. The low drug bioavailability from the oral and rectal preparations (84) may mean that large doses will be needed to suppress emesis resulting from C T Z stimulation. Present data indicate that dosing with rectal suppositories appears most efficacious (43), but dosing should commence at least 4 h prior to chemotherapy (84).…”
Section: Domperidonementioning
confidence: 99%